PENGARUH KARAKTERISTIK INDIVIDU, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Suhandra Makkasau (Al-Amwal : Journal of Islamic Economic Law, 2021)
This study aims to determine how the influence of individual characteristics, work environment and work discipline on employee performance. In this case, the individual characteristics possessed by employees support the achievement of employee performance levels, the better the individual characteristics are shown by the better, the behavior, interests, abilities and attitudes possessed and developed by the employees of PT. Sumber Graha Sejahtera Branch of Luwu Regency. From the results of hypothesis testing conducted shows that the individual characteristic variables, work environment and work discipline together have a significant effect on employee performance at PT. Sumber Graha Sejahtera Branch of Luwu Regency. This is evidenced by testing the hypothesis using the F statistical test (simultaneous), the t value of 82.705 is greater than the F table value of 2.866 and the significance probability value of 0.000 is less than 0.05 with a percentage of influence of 87.30% while the rest influenced by other factors not examined in this study. In other words, the fourth hypothesis states that individual characteristics, work environment and work discipline simultaneously have a significant effect on employee performance.